Social justice through public sector / by Raj K. Nigam - "Nigam, Raj K." (New Delhi, 1976)
The Papers included in this publication bring out the important role played by the public sector in accelerating the pace of socio-economic transformation in India. This sector of economic activity was started by our First Prime Minister, Mr. Jawaharlal Nehru, on a modest scale, but during the last 10 years of Mrs. Indira Gandhi's leadership, it has become a dominant force in the national economy. The country expects a firm and abiding commitment from the management and workers of the enterprises ; whether in the public or private sector.
Keywords: Government business enterprises